Allocation of thermal imaging camera: Promoting efficient movement in entrepreneur workplace (ARTEKS : Jurnal Teknik Arsitektur, 2022)
The pandemic COVID-19 has been a disaster for all over the world. The significant changes caused by the pandemic has left a huge impact on every sector especially on business environment and caused a major economic shock. In this paper, the role of technology- Thermal Imaging Camera (TIC) has been explore and discuss in achieving a proposed studies to preventing and decreases the spreading of virus in efficient way. From this point of view, the proposed study has contributed to working environment –entrepreneur workplace. The working environment has been a high risk in virus spreading since it involved in people interaction’s place. Thus, TIC is important to prevent the virus spreading in workplace and community. The study of efficient movement and the issue regarded appropriate location of TIC in entrepreneur workplace has been carried in this paper. The objectives of this study are to identify the requirement of Thermal Imaging Camera (TIC) in entrepreneur workplace zoning, to determine the best location for Thermal Imaging Camera (TIC) in entrepreneur workplace zoning and to study the Thermal Imaging Camera (TIC) location in promoting efficient workplace movement. The literature review is carried out to determined the related issues: TIC, workplace zoning and efficient movement I entrepreneur workplace. the qualitative method by John Creswell is used in collecting data to identify the best position of TIC in entrepreneur workplace by using observation method. As conclusion, the study for practice of allocate the TIC in the best location in entrepreneur workplace promotes the efficient of movement which it gives a direct and indirect impact on workplace performance.
Keywords: Efficient movement; Thermal imaging camera (TIC); Workplace zoning